Islam and the army in colonial India Sepoy Religion in the service of empire - Green, Nile (Cambridge studies in Indian history and society, 2009)
Set in Hyderabad in the mid-nineteenth and early twentieth centuries, this book, a study of the cultural world of the Muslim soldiers of colonial India, focuses on the soldiers' relationships with the faqir holy men who protected them and the British officers they served. Drawing on Urdu as well as European sources, the book uses the biographies of Muslim holy men and their military followers to recreate the extraordinary encounter between a barracks culture of miracle stories, carnivals, drug-use and madness with a colonial culture of mutiny memoirs, Evangelicalism, magistrates and the asylum. It explores the ways in which the colonial army helped promote this sepoy religion while at the same time attempting to control and suppress certain aspects of it. The book brings to light the existence of a distinct 'barracks Islam' and shows its importance to the cultural no less than the military history of colonial India.